Capacity Building in the HNP Sector : Implementing the Strategic Options for Better Health in Africa - Preker, Alexander S.; Kassak, Kassem; Amponsah, Kofi; Dussault, Gilles (World Bank, Washington, DC, 2013)
The Africa region has the highest burden of disease and lowest spending levels per capita on health care in the world. Achieving better health and protecting people against the impoverishing effects of illness requires both more money and better spending. Capacity building will be central to achieving these objectives. This report recommends an expanded definition of capacity building to include strengthening of the underlying institutions and organizations, in addition to the traditional focus on management and infrastructure. This includes ensuring that there is a strong government role in the stewardship function, that sustainable financing is channeled through risk sharing arrangements, that input generation takes full advantage of the drive and innovation of the private sector, and that service providers are allowed the autonomy and required accountability to provide high quality care for specified population groups. The also report analyzes activities undertaken through Bank operations, ESW and WBI since the beginning of 1990s, selected case studies, and focus group interviews; summarizes lessons learned (successes and failures); and makes recommendations on the way forward.